Youth and Creativity Center Medan-Selayang (With Neo-Vernacular Architecture Design Approach) - Imam Faisal Pane; Hilda Masito Tanjung (International Journal of Architecture and Urbanism, 2018)
The construction of facilities such as Youth and Creative Center is to meet the needs facilities and urban infrastructure. As a container that enables youth to engage in positive activities to appreciate themselves, exchanging ideas and channeling energy, hobbies, and ideas shared by local youth. Strategically located on the outskirts of Medan City and located in the city center of education, the presence of the youth center is expected to take a role in the local moral and social control of the teenager which has increased annually, and hopes to someday cope with the social problems that often arise; such as fights between students, theft, vandalism, and drug with prevention to turn into a quality generation. With the existence of Youth and Creativity Center Medan-Selayang, is expected to adapt to the characteristics of teenagers who are always evolving progress of time, can interact, and be creative with others positively and in an integrated environment between education, recreation, and sport, which is useful and convenient to use. Teenagers Youth and Creativity Center is using the Neo-Vernacular Architecture design approach, which impressed magnificent and sturdy. Therefore the concept of the shape taken is a square geometric shape, and the overall shape shows the symmetrical shape.